Work stress prevention needs of employees and supervisors - Bo M. Havermans; Evelien P. M. Brouwers; Rianne J. A. Hoek; Johannes R. Anema; Allard J. van der Beek; Cécile R. L. Boot (BMC, 2018)
Abstract Background Work stress prevention can reduce health risks for individuals, as well as organisational and societal costs. The success of work stress interventions depends on proper implementation. Failure to take into account the needs of employees and supervisors can hinder intervention implementation. This study aimed to explore employee and supervisor needs regarding organisational work stress prevention. Methods Semi-structured telephone interviews were conducted with employees (n = 7) and supervisors (n = 8) from different sectors, such as the finance, health care, and services industry. The interviews focused on respondents' needs regarding the prevention of work stress within an organisational setting. Performing thematic analysis, topics and themes were extracted from the verbatim transcribed interviews using Atlas.ti. Results Both employees and supervisors reported a need for: 1) communication about work stress, 2) attention for determinants of work stress, 3) supportive circumstances (prerequisites) for work stress prevention, 4) involvement of various stakeholders in work stress prevention, and 5) availability of work stress prevention measures. Both employees and supervisors expressed the need for supervisors to communicate about work stress. Employees and supervisors reported similar psychosocial work factors that should be targeted for prevention (e.g., social support and autonomy). There was greater variety in the sub-themes within communication about work stress and supportive circumstances for work stress prevention in supervisor responses, and greater variety in the sub-themes within availability of work stress prevention measures in employee responses. Conclusions Both employees and supervisors were explicit about who should take part in communication about work stress, what prerequisites for work stress prevention should exist, and which stakeholders should be involved. These results can inform work stress prevention practice, supporting selection and implementation of interventions. Trial registration This study was registered in the Netherlands National Trial Register, trial code: NTR5527.